A COMPARISON OF HEAT PERFORMANCE BETWEEN GREEN ROOFS ON CONCRETE AND GREEN ROOFS ON CORRUGATED ZINC - Sri Yuliani; Gagoek Hardiman; Erni Setyowati (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2020)
Green roofs are generally applied to concrete roofed buildings. This study compares the thermal performance of green roofs that occur in corrugated concrete and zinc to expand green roof innovation. The study experimented on a method using the 2011 Ecotect computer simulation. The results showed that the difference in temperature reduction in corrugated zinc was higher than in concrete. Changes in heat outside the roof space on both have a number that has a relatively small difference, but the difference in heat is visible in the inner space. Based on the thermal performance of the roof, the use of corrugated zinc roofs as the base of the green roof in the building could be an alternative green roof material besides concrete.